Model Pemberdayaan Industri Batu Bata Dan Genteng Di Kabupaten Sarolangun Provinsi Jambi - Dahmiri Dahmiri (Jurnal Studi Manajemen dan Bisnis, 2014)
The result shows that the empowerment level of coal mining industry and roof tile in Sarolangun regency are still low. The empowerment indicator consists of business access, market, human resource and technology. Based on FGD and in-depth interview with the key persons, it can be found that considering the business access could increase the empowerment. This can be done through management training and production creativity on credit loan with low interest, providing home trade in market access, marketing and exposing market opportunities, increasing technical skill by training on human resource, providing training to develop entrepreneur skill, offering an instructor, building an education institute and technological access by giving reachable technology, proposing patent’s counseling and consultation.